Pengaruh Penataan Pola Tempat Duduk Terhadap Interaksi Komunikasi dan Pemahaman Keberagaman Budaya Peserta Didik Kelas 4 UPT SP SDN 268 Towuti - Hijriah, Fitrah Nur; Rustam, Edhy; Suryani, Lilis (Jurnal Ilmiah Global Education, 2025)
The research is grounded in the importance of classroom physical environments in creating a conducive learning atmosphere and promoting broader social interactions. This study aims to analyze the influence of seating arrangement patterns on students’ communication interaction and understanding of cultural diversity in Grade IV at UPT SP SDN 268 Towuti. Initial observations revealed limited interaction among students, who mostly communicated only with their seatmates. Therefore, a strategic seating arrangement approach is needed to enhance engagement and cultural awareness among students.This study employs a quantitative approach using path analysis. The subjects were 27 fourth-grade students. Data were collected through documentation and questionnaires, both of which were tested for validity and reliability. Data analysis was conducted using multiple linear regression and t-tests. The results indicate that seating arrangement patterns have a significant influence on both communication interaction and students’ understanding of cultural diversity. Group-based seating arrangements proved to be the most effective in fostering student interaction and enhancing their appreciation of diversity. These findings align with Vygotsky’s constructivist theory, which emphasizes the role of social interaction in learning, and with Johnson & Johnson’s perspective on the importance of group cohesion in developing tolerance and empathy in the classroom. Therefore, it is recommended that teachers implement collaborative seating arrangements and that schools support flexible classroom layouts.